2020
DOI: 10.1016/j.bpj.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased Stiffness Inhibits Invadopodia Formation and Cell Migration in 3D

Abstract: Cancer cells typically invade through basement membranes (BMs) at key points during metastasis, including primary tumor invasion, intravasation, and extravasation. Cells extend invadopodia protrusions to create channels in the nanoporous BM through which they can invade, either via proteolytic degradation or mechanical force. Increased matrix stiffness can promote cancer progression, and two-dimensional (2D) culture studies indicate that increased stiffness promotes invadopodia degradation activity. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 59 publications
(83 reference statements)
0
29
0
Order By: Relevance
“…The heatmap indicates that the invadopodia extension length decreases as elastic modulus increases (purple arrow in Figure 4H) due to the larger resistance encountered by invadopodia in stiffer ECMs. Interestingly, by utilizing the same type of IPN hydrogels of varying elastic stiffnesses (low stiffness [LS], medium stiffness [MS], high stiffness [HS], and very high stiffness [VHS]; see STAR Methods) (Chang et al, 2020), we found that cells have shorter invadopodia lengths in stiffer ECMs (Figures 4F and 4G). By varying the model parameter associated with stiffness (i.e., elastic modulus E 0 ), we can quantitatively fit the model to the experimental data.…”
Section: Viscoplasticity Facilitates Invadopodia Oscillations By Softening Ecm Over Repeated Cyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…The heatmap indicates that the invadopodia extension length decreases as elastic modulus increases (purple arrow in Figure 4H) due to the larger resistance encountered by invadopodia in stiffer ECMs. Interestingly, by utilizing the same type of IPN hydrogels of varying elastic stiffnesses (low stiffness [LS], medium stiffness [MS], high stiffness [HS], and very high stiffness [VHS]; see STAR Methods) (Chang et al, 2020), we found that cells have shorter invadopodia lengths in stiffer ECMs (Figures 4F and 4G). By varying the model parameter associated with stiffness (i.e., elastic modulus E 0 ), we can quantitatively fit the model to the experimental data.…”
Section: Viscoplasticity Facilitates Invadopodia Oscillations By Softening Ecm Over Repeated Cyclesmentioning
confidence: 99%
“…Alginate molecular weight (MW) and cross-linker concentration were varied in order to form a set of IPNs with initial elastic moduli of around 1.8 kPa but varying mechanical plasticity (Wisdom et al, 2018). In addition, calcium crosslinking of the alginate matrix was varied to form a set of IPNs with different elastic moduli, i.e., low stiffness 0.4 kPa (LS), medium stiffness 1.5 kPa (MS), high stiffness 4.4 kPa (HS), and very high stiffness 9.3 kPa (VHS) (Chang et al, 2020).…”
Section: Preparation Of Viscoplastic Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is time to improve traditional cell culture to better simulate the complex environment in vivo (Pampaloni et al, 2007;Duval et al, 2017). The 3D cell culture models have emerged for studying cancer cell invasion so far, which better imitates the internal environment (Chung et al, 2009;Engel et al, 2015;Wagner et al, 2019;Chang et al, 2020). Due to the variability of morphology and the excellent biocompatibility, hydrogels are widely used in many kinds of research about cell migration in 3D environments (Sugimoto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[31,30,32] Chang et al showed that increased stiffness physically restricted invadopodia extension and cell migration in 3D, which presented inconsistent tendency compared to the results in 2D. [33] Vasudevan et al proposed biomimetic ECMs with independently tunable stiffness to demonstrate the distinct cell migratory patterns due to differences in matrix stiffness. [29] Hadden et al fabricated polyacrylamide hydrogels with graded stiffness to study how human adipose-derived stem cells performed in such environments, and the results showed that stem cells tended to move toward stiffer regions.…”
Section: Introductionmentioning
confidence: 99%